The challenges faced by community learning center program in community literacy development: Iran as a case study - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Ali (Scientia Socialis, 2009)
Literacy has played a very important role in Community Development. Without literacy; people have difficulties improving their quality of lives. Iran is no exception. For this reason, Iran has implemented the various literacy programs. One of the programs is Community Learning Center Program (CLCP). So far, CLCP has been implemented into 3517 communities in the country. Therefore, the general objective of this study was to examine the challenges faced by Community Learning Center Program (CLCP) in Community Literacy Development (CLD) while the specific objective of this study was to describe the necessary actions to strengthen the CLCP in CLD.